Correctness analysis of the irradiation creep equations considering the voids growth in the material using the modified Huang equation - Chirkov, O. Yu. (Reports of the National Academy of Sciences of Ukraine, 2022)
The authors have investigated the correctness conditions of the defining equations of irradiation creep that consider the voids volume increase in the material by the modified Huang equation. The equation involves the Rice-Tracey- Huang models, where the additional continuous function is introduced depending on the stress state stiffness, and it has a continuous derivative greater than zero. Using the modified Huang equation allows one to enhance the properties of the defining equations to analyze the porosity of irradiated material facilitating the relaxation of constraints on the initial data related to the stress state stiffness. The modern models of irradiation swelling and creep are considered. They account for the damaging dose, irradiation temperature, and stress state effect on the processes of swelling and creep of the irradiated material. To analyze the behavior of the porous material under neutron irradiation, the equations of irradiation creep are used. In the equations, irreversible deformations include instantaneous plastic deformations, radiation swelling deformations, radiation creep deformations, and structural volume deformations considering the voids concentration in the material according to the modified Huang equation. The analysis of the properties of the defining equations allows one to formulate the conditions under which the dissipation intensity and the power which is developed by the additional stresses on the additional deformations do not decrease during the loading of the porous material exposed to the neutron irradiation. Based on the obtained energy inequalities generalizing the Drucker strengthening postulate for the irradiated porous material, the conditions are established that ensure the correctness of the defining equations of irradiation creep, which consider the growth of porous fracture concentration according to the modified Huang equation.